The gardener and the carpenter : what the new science of child development tells us about the relationship between parents and children - Gopnik, Alison (2016)
"Alison Gopnik, a leading developmental psychologist, illuminates the paradoxes of parenthood from a scientific perspective"--
Includes bibliographical references (pages 265-287) and index.
Keywords: Developmental psychology; Child psychology; Parenting; PSYCHOLOGY / Developmental / Child